Neuroprotective Effects of High-Intensity Interval Training through Neuroplastic Changes in a Restraint Stress-Induced Depression Model - Dong-Joo Hwang; Hyun-Seob Um; Dong-Hun Choi; Joon-Yong Cho (Applied Sciences, 2023)
This study aimed to analyze the neuroprotective effects of various exercise intensities in a mouse model of depressive behavior disorders. Seven-week-old male C57BL/6 mice were divided into a control group, depressive disorder group (RST), moderate-intensity sustained exercise group (RST_MICT), high-intensity sustained exercise group (RST_HICT), and high-intensity interval exercise group (RST_HIIT). The animal model was established by applying restraint stress (RST) at 2 h/day for 14 days. Behavioral function was better in all exercise groups, especially in the RST_HIIT group, than in the RST group. Factors related to brain-derived neurotrophic factor showed higher levels in the exercise groups than in the RST group. The levels of 4-hydroxynonenal, an oxidative stress index, were significantly lower in the exercise groups than in the RST group. Malondialdehyde levels were lower in the exercise groups than in the RST group, but the difference was not significant. The analysis of serotonin and corticosterone, indicators of depression, revealed positive results in the exercise groups. The neuroplasticity-related variables c-fos and glial fibrillary acidic protein were more positive in the RST_HIIT group than in the RST group. Thus, HIIT improved neuroplasticity, oxidative stress, and neurotrophic factors in the depressive disorder model, indicating its potential for preventing and treating depression.